2018
DOI: 10.1093/eurheartj/ehy004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of treatment delay on mortality in ST-segment elevation myocardial infarction (STEMI) patients presenting with and without haemodynamic instability: results from the German prospective, multicentre FITT-STEMI trial

Abstract: AimsThe aim of this study was to investigate the effect of contact-to-balloon time on mortality in ST-segment elevation myocardial infarction (STEMI) patients with and without haemodynamic instability.Methods and resultsUsing data from the prospective, multicentre Feedback Intervention and Treatment Times in ST-Elevation Myocardial Infarction (FITT-STEMI) trial, we assessed the prognostic relevance of first medical contact-to-balloon time in n = 12 675 STEMI patients who used emergency medical service transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
194
0
21

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 291 publications
(238 citation statements)
references
References 29 publications
5
194
0
21
Order By: Relevance
“…198 A recent analysis of 12 675 STEMI patients in the FITT-STEMI (Feedback Intervention and Treatment Times in ST-Elevation Myocardial Infarction) trial emphasizes the strong impact of time delays on mortality, particularly in STEMI patients with cardiogenic shock or out-of-hospital cardiac arrest. 199 In shock without out-ofhospital cardiac arrest, every 10 min treatment delay between 60-180 min from the first medical contact resulted in 3.3 additional deaths per 100 PCI-treated patients, and in 1.3 additional deaths after out-of-hospital cardiac arrest without cardiogenic shock. In stable STEMI patients, time delays were substantially less relevant (0.3 additional deaths per 100 PCI-treated patients for every 10 min delay between 60-180 min from the first medical contact).…”
Section: Time Delaysmentioning
confidence: 99%
“…198 A recent analysis of 12 675 STEMI patients in the FITT-STEMI (Feedback Intervention and Treatment Times in ST-Elevation Myocardial Infarction) trial emphasizes the strong impact of time delays on mortality, particularly in STEMI patients with cardiogenic shock or out-of-hospital cardiac arrest. 199 In shock without out-ofhospital cardiac arrest, every 10 min treatment delay between 60-180 min from the first medical contact resulted in 3.3 additional deaths per 100 PCI-treated patients, and in 1.3 additional deaths after out-of-hospital cardiac arrest without cardiogenic shock. In stable STEMI patients, time delays were substantially less relevant (0.3 additional deaths per 100 PCI-treated patients for every 10 min delay between 60-180 min from the first medical contact).…”
Section: Time Delaysmentioning
confidence: 99%
“…In ST-elevation myocardial infarction (STEMI), it was revealed that the mortality rate is higher if the time from the first contact with medical staff to the reperfusion by catheterization is delayed. It was reported that the 3.3% mortality rate increases with each 10-min delay in cardiogenic shock [16]. Even in acute heart failure, the death rate increases as the time to hospitalization is delayed [17,18].…”
Section: History Of Coronary Care Unit and Its Achievementsmentioning
confidence: 99%
“…Patients with acute heart failure and cardiogenic shock were quickly transported to an expert center before it became severe, then prepared for respiratory and circulation management before admission through the medical team that was familiar with rapid diagnosis and treatment [18,20]. For STEMI with cardiogenic shock, the 12-lead electrocardiogram and information on the severity are reported from the ambulance so that the catheterization room and percutaneous cardiopulmonary support (PCPS) and Impella (Abiomed, Danvers, MA, USA) [21] will be prepared [16,18].…”
Section: History Of Coronary Care Unit and Its Achievementsmentioning
confidence: 99%
“…[11][12][13][14] In the decades since, in-hospital survival rates have plateaued while the incidence of AMI CS and acute decompensated heart failure (ADHF) CS has increased despite improvements in door-to-balloon times (the cardiovascular specialist's version of the surgeon's 'Golden Hour') and adjunctive pharmacotherapy. [15][16][17][18][19][20][21][22][23][24][25][26][27][28] Early survivors also suffer unacceptably high rates of post-discharge heart failure, rehospitalisation and death. [29][30][31][32] Revascularisation is necessary but not sufficient for survival in AMI CS.…”
mentioning
confidence: 99%